Legal Protection Against Substitute Notary in Semarang Based on Act No. 2 of 2014 Amendment Act No. 30 of 2004 concerning Notary - Setyawati Setyawati; Putri Nofita S Nofita S; Fahrurroji Sidik (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2020)
The purpose of this study are to: 1) to identify and analyze the implementation of the legal protection of Substitute Notary in Semarang based on Act No. 2 of 2014 amendments to the Act No. 30 Of 2004 on Notary. 2) to identify and analyze the constraints and solutions on the legal protection of Substitute Notary in Semarang based on Act No. 2 of 2014 amendments to the Act No. 30 Of 2004 on Notary.Based on the results of data analysis concluded that: 1) the implementation of the legal protection of Substitute Notary in Semarang based on Act No. 2 of 2014 amendments to the Act No. 30 of 2004 concerning Notary, that the authority and obligation Substitute Notary has the same status as Notary Public. Substitute Notary Public Notary and is common in performing official duties stipulated by the Act. 2) Obstacles and solutions on the legal protection of Substitute Notary in Semarang based on Act No. 2 of 2014 amendments to the Act No. 30 of 2004 concerning Notary, Professional Notary protected by the Honorary Council of Notaries that served to protect the profession Notary not Notary personal, Notary Honorary Council oversees only ethical behavior Substitute Notary Public Notary and regulated in UUJN, Perkemenkumham and Notary Code of Ethics, and preferably Substitute Notary must always adheres to the rule of law that is UUJN, Perkemenkumham and Notary Code. If all rules are fulfilled, Substitute Notary will be free from claims filed her form.Keywords: Legal Protection; Substitute Notar; UUJN.